Estrategias de marketing para la promoción turística de la parroquia Mulaló - Almache Tapia, Jessica Estefanía (2017)
The present research project had as purpose to perform marketing strategies to boost the tourism industry of the parish Mulaló, allowing by this way to create new sources of employment taking advantage of the existence of the same. The essential problem is the lack of exploitation of the places that the parish have itself that is generated by the lack of implementation of marketing strategies, which prevents learn the different tourist attractions with which it has. For this reason the elaboration of the situational diagnosis of the parish was essential in order to identify the strengths, weaknesses, opportunities and threats, since these were very useful to determine the most appropriate strategies that allowed promote the inventory of tourism. Used a methodology of adequate investigation that helped the collection of effective information and needed to support a possible solution to the problem and inconvenience detected in the parish Mulaló. The objective of the research was to design marketing strategies that helped to exploit the natural resources that has, taking advantage of the great biodiversity that exists in this area, with the aim of capturing and engage potential tourists, through the strategies outlined to promote and enhance all the sights that has parish Mulaló. Achieving this way to improve the lifestyle of the habitants surrounding these touristic sites.